EFEKTIVITAS MEDIA PEMBELAJARAN POWER POINT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA - Srimaya Srimaya (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
This study was a classroom action research. This study employed learning media of powerpoint. This media provided five facilities such as (1) design template, that can be applied for presentation one of which an animation, (2) custom show, that a file of presentation can be created in several versions, (3) office art, that provided a special graphic, (4) graphic file format, that can save picture file, and (5) delivering presentation, that provided easier presentation in any ways. The learning media was provided to improve students’ learning motivation which was expected to improve students’ activity and students’ learning achievement.The goal of this study was to examine the effectiveness of learning Biology of high school student trough the learning media of powerpoint. The objectives of this study were to examine (1) the effectiveness of the learning media of powerpoint through the score of learning motivation of Biology of high school students at class XI IPA 3 SMAN 1 Pangkajene, (2) the effectiveness of learning media of powerpoint through the observation of learning activity of Biology of high school students at class XI IPA 3 SMAN 1 Pangkajene, and (3) the effectiveness of learning media of powerpoint through the learning achievement of Biology of high school students at class XI IPA 3 SMAN 1 Pangkajene.The result of this study revealed that (1) students’ learning motivation was improved viewed from the indicator of achievement of students’ motivation after the treatment where statistically it was obtained 100% students was in high category, (2) the learning media of powerpoint improved students’ learning activity, and (3) students’ learning achievement of Biology at class XI IPA 3 SMAN 1 Pangkajene was improved. Those improvements can be seen from the average of evaluation test in cycle I which was 47,52 and in cycle II improved to 79,92. Moreover, the achievement of minimum mastery criteria (KKM) showed frecuenci 28 (87,5%) students obtained the score 75 the set KKM score which was.